Make Your Students Sweat: Fitness Integrated Learning in Business Education - Haber, Julita; O’Connor, Genevieve Elizabeth; Sarkar, Nina (Journal of Applied Business and Economics, 2016)
In this exploratory study, we propose a new pedagogy for teaching business courses—Fitness Integrated Learning (FIL). Our FIL modality of course instruction embeds physical education into an existing college-level business course curriculum for the purpose of enhancing students’ cognitive performance and student experience. Drawing from research literature on fitness and education as well as our own exploratory study of applying three major FIL-modalities in four college campuses in the Northeast, we formulate a conceptual FIL model and offer a theoretical framework to test our propositions. We conclude by offering a research design to test a full FIL-structured course.